Demographics, Clinical Profile and Outcome among the HIV Infected Persons Hospitalized in the HAART Era in Barbados. - Kumar, Alok; K Kilaru, Rajesh; Forde, S; Kumari, Geeta; Roach, T; Singh, Keerti; L Nielsen, Anders (Journal of Clinical Research In HIV AIDS And Prevention, 2013)
Background: HAART has resulted in significant decline in morbidity and mortality from HIV. However, it is unclear if the trends have continued in the current HAART era. An understanding of healthcare utilization patterns is important for optimization of care and resource allocation. We examined the diagnoses for hospitalizations of patients with HIV and their clinical and demographic profile years after the introduction of HAART. Methods: A retrospective audit of the HIV admissions from July 2009 through June 2010. The case notes of all the adult admissions where one of the discharge diagnoses was HIV infection was reviewed. Data including the demographics, date of diagnosis, treatment and the follow up details, admission outcome and the final diagnosis were extracted from the case notes. Results: Over the 12 months period there were 154 admissions where one of the discharge diagnosis was HIV infection, and this accounted for 2.9% of all medical admissions in adults. 103(67%) admissions were in persons who were known to be HIV infected prior to the current admission. HIV infection was diagnosed for the first time during the current admission in 51(33%) cases. Nearly two-thirds of those hospitalized, had a CD 4 cell counts of < 200/µL and 63 (66%) had a viral load greater than 50,000 copies/ml. Over all, opportunistic infection was the commonest (47%) discharge diagnosis, followed by serious bacterial infections and HIV nephropathy. The median duration of hospitalization was 6 days (Range 2 to 71 days). There were 49 (32%) deaths. Conclusions: A significant proportion of patients admitted with HIV infection were still diagnosed on admission and were found to be severely immunosuppressed. An opportunistic infection continues to be the commonest discharge diagnosis in HIV infected patients.
Keywords: HIV/AIDS; Hospitalization; HAART era